Preventive effects of tocotrienol-enriched mixed fraction on plaque formation and stability in early and established atherosclerosis - Effat Omar; Nurul Aishah Muhammad; Nurul Ain Abu Bakar; Hapizah Nawawi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Atherosclerosis is the underlying pathology for cardiovascular disease. The preventive effects of tocotrienol-enriched mixed fraction (TEMF) on atherogenesis remain unclear. Objective: To investigate the preventive effects of TEMF supplementation on early and established atherosclerosis. Methods: Twenty New Zealand white rabbits were divided into TEMF (n=10) and placebo (n=10) groups. Treatments were given by oral gavage for 8 weeks followed by a 1% high cholesterol diet (HCD) for another two (to induce early atherosclerosis) or eight weeks (established atherosclerosis). At the end of the study, the aorta was dissected, stained with Sudan IV, and qualitatively analyzed for the atherosclerotic lesion. Immunohistochemistry was performed to detect expression of interleukin-6 (IL-6), CRP, nuclear factor kappa beta, E-selectin, intercellular adhesion molecule-1 (ICAM- 1), vascular cell adhesion protein-1 (VCAM-1), smooth muscle actin (SMA), and matrix metalloproteinase-12 (MMP-12). Results: In both early and established atherosclerosis groups, there was a significant reduction of atherosclerotic lesions in TEMF compared to placebo. Atherogenic biomarkers; IL-6, CRP, E-selectin, SMA, and MMP-12 were reduced with TEMF supplementation in established atherosclerosis (p<0.05). Neutral effects were seen in the early atherosclerosis group. Conclusion: TEMF supplementation in the preventive setting decreased atherosclerosis formation and reduces endothelial inflammation in established atherosclerosis lesions while increasing plaque stability.